Filogenia de Haltichellini Ashmead, (Hymenoptera, Chalcididae, Haltichellinae) - Tavares, Andrea Barbieri Navarro (2013)
Haltichellini is worldwide and assemble 29 genera and 376 species. Most of its generais unsatisfactorily defined and delimited, which has lead instability in the species classification and difficulties in their identification. This study presents the first cladistic analysis for the tribe and based on a representative sample of the world's fauna. This analysis aimed to evaluate the genera and to generate basis to propose a generic classification according to the cladistic relationships among its species.We assessed the monophyly of 24 from the 29 valid genera, based on 97 morphological characters, 54 unpublished ones. The results indicated that: Belaspidiais monophyletic and external to Haltichellini; from 14 genera with more than one species, seven were reported as monophyletic (Aphasganophora, Aspirrhina, Euchalcis, Neochalcis, Tainaniella, Tanycoryphus and Uga); Allochalcis was indicated as paraphyletic; and six genera were 6 indicated as polyphyletic (Antrocephalus, Haltichella, Hockeria, Kriechbaumerella, Oxycorypheand Rhynchochalcis).Based on these relationships, it was found the necessity of following nomenclatural adjustments and propositions: a new genus; ten generic synonyms; two revisions of generic status; 41new combinations; and revalidation of five combinations. Twenty-one genera are redefined. Description and identification key to genera studied, and illustrations for the characters analyzed are presented